A modelling framework and R-package for evaluating system performance under hydroclimate variability and change. (May 2021) - Bennett, Bree; Devanand, Anjana; Culley, Sam; Westra, Seth; Guo, Danlu; Maier, Holger R.
Abstract: Effective implementation of a scenario-neutral climate impact assessment relies on the integration of many modelling components at multiple stages: from the generation of appropriate climate boundary conditions that can be used to rigorously 'stress-test' a system, to the simulation, visualisation and interpretation of resulting system performance. For systems with complex temporal dynamics, the generation of climate forcing time series combined with the significant simulation and visualisation demands represent a barrier to the wide-scale adoption of scenario-neutral approaches. A unified five-step framework and supporting R-package, fore SIGHT (Systems Insights from the Generation of Hydroclimate Time series), are introduced that enable the application of a scenario-neutral climate impact assessment from appropriate time series generation to the analysis of system performance. The software can be applied to compare both current system performance and selected alternative system management or design options and its application is demonstrated for a case study. Highlights: A five-step framework for scenario-neutral climate impact assessment is introduced. An R-package has been developed to implement the presented five-step framework. Supports each step from timeseries generation to evaluating system options.